Career Development of Students through Information Services to Support Decision Making for Further Studies at Madrasah Aliyah Deli Serdang - Abdillah, Risyad Fikri; Nurhayani, Nurhayani (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
This research aims to determine student career development thourgh information services to assist decisions making for further studies. This research uses a qualitative method with a descriptive approach. The data collection tools used in this research were in-depth interviews, Participatory observation and documentation studies. The research subjects chosen were 3 BK teachers as secondary data informant and 10 class XII Religion students as primary data informant. Data analysis was carried out using the Miles and Huberman model, namely: data reduction, data presentation and drawing conclusions. The validity of the data in this research is credibility (internal validity), transferability (external validity), dependability (reliability), and confermability (objectivity). The research results show that information services that are routinely carried out every week has a positive impact on career students development in making decisions about further studies. Information services are the services most frequently implemented at MAN 1 Deli Serdang. Information services are a supporting indicator for career guidance and counseling teachers provide information about universities, study programs, jobs or things that students do after completing themselves at Madrasah Aliyah (MA). This help student develop their career and determine further study options. Student stated that they gained a good understanding after carrying out information services by the BK teacher so that they could determine further study and job prospect for themselves and felt motivated so as to increase their abilities and potential in accordance with the decision to further study for career development.